2012
DOI: 10.2174/156800912802429364
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Signature for Oncogenic BRAF in Human Colon Cancer Cells is Revealed by Microarray Analysis

Abstract: Sporadic colorectal cancer develops through a number of functional mutations. Key events are mutually exclusive mutations in BRAF or RAS oncogenes. Signatures for BRAF oncogene have been revealed in melanoma. In a previous study we have reported a molecular signature for HRAS and KRAS mutations in colorectal cell lines that also showed an EMT phenotype for HRAS. In this study we report a molecular profile for a BRAF oncogenic mutation BRAFV600E in colon using the Illumina 45,000 gene microarray. Key differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…In addition to mutations in the BRAF gene, lesions of the serrated pathway are also characterized by high frequency of MSI and CIMP [28] , [29] , [30] . Our gene expression analysis has identified 744 genes that were differentially expressed between MVHP and SSA/P stratified by BRAF V600E mutation status (adjusted P < .05, fold change ≥ ± 2), providing convincing evidence that these polyp types are most likely derived from distinct molecular pathways, which is consistent with other published reports [9] , [11] , [12] , [13] , [31] . Several studies have attempted to identify biomarkers of SSA/P to develop a diagnostic tool to assist the pathologist to correctly diagnose this polyp type or to expand our knowledge on biology and underlying molecular events involved in malignant transformation of these lesions [8] , [9] , [10] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to mutations in the BRAF gene, lesions of the serrated pathway are also characterized by high frequency of MSI and CIMP [28] , [29] , [30] . Our gene expression analysis has identified 744 genes that were differentially expressed between MVHP and SSA/P stratified by BRAF V600E mutation status (adjusted P < .05, fold change ≥ ± 2), providing convincing evidence that these polyp types are most likely derived from distinct molecular pathways, which is consistent with other published reports [9] , [11] , [12] , [13] , [31] . Several studies have attempted to identify biomarkers of SSA/P to develop a diagnostic tool to assist the pathologist to correctly diagnose this polyp type or to expand our knowledge on biology and underlying molecular events involved in malignant transformation of these lesions [8] , [9] , [10] .…”
Section: Discussionsupporting
confidence: 89%
“…Molecular studies including gene expression profiling comparing different subsets of CRC precursor lesions have advanced our knowledge on the molecular events occurring during the neoplastic progression in these lesions, providing additional support for distinct molecular pathways involved in tumorigenesis of this subset of CRC [7] , [8] , [9] , [10] . Recent gene expression analysis of serrated and conventional colorectal carcinomas has also suggested that CRCs developing through the serrated pathway may require different chemotherapy treatment regimes [11] , [12] , [13] . This is further supported by recent studies that demonstrated colorectal adenocarcinomas characterized by the BRAF V600E mutation have significantly worse overall survival when compared to BRAF wild-type or KRAS mutated adenocarcinomas [3] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies proved that Ihh functions as an antagonist of Wnt signaling during colorectal tumorigenesis, and the Hh signaling pathway was recently shown to antagonize the constitutive activity of Wnt pathway that drives proliferation and metastasis of CRC cells, thus establishing an initial antagonizing counterpart between Ihh and Wnt pathways 12,15,33,37. In human CRC, enhanced Gli1 represses Wnt-TCF targets and is involved in the metastasis of CRC 101105.…”
Section: Hh Signaling Pathway In Crcmentioning
confidence: 99%
“…Microarray data derived from these studies can validate and further interprete data derived by analysis of clinical samples. Comparison between BRAFV600E signature analyzed [ 124 ] with another study where a RASV12 signature was demonstrated [ 125 ], shows that their gene expression signatures can pinpoint interesting mechanistic differences between these two frequently mutated oncogenes in CRC. Regarding apoptosis and nucleotide excision repair, oncogenic BRAF upregulates caspase 6 and downregulates XPC and ERCC1, which is not the case for oncogenic KRAS [ 124 , 125 ].…”
Section: Differential Impact Of Kras Vs Braf Oncogenes In Disease Diamentioning
confidence: 99%